2021
DOI: 10.3390/diagnostics11081413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Teleradiology Technology for Image-Based Distant Consultations: Applications in Neurosurgery

Abstract: In emergency settings, fast access to medical imaging for diagnostic is pivotal for clinical decision making. Hence, a need has emerged for solutions that allow rapid access to images on small mobile devices (SMD) without local data storage. Our objective was to evaluate access times to full quality anonymized DICOM datasets, comparing standard access through an authorized hospital computer (AHC) to a zero-footprint teleradiology technology (ZTT) used on a personal computer (PC) or SMD using national and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Consultation of persons suspected of infection or infectious disease or those diagnosed with infection or infectious disease may be based on the results of tests available remotely [11] and can take place, particularly in large hospitals with a dispersed structure or between branches [61], especially in the initial phase, with the use of teleconferences or teleconsultations, supported by the hospital it system, securely transmitted between medical data units, as it is already practiced by multiple medical specialties [62][63][64] -which is conducive to the speed of response to the occurring circumstances and changes in the epidemiological situation [41].…”
Section: Resultsmentioning
confidence: 99%
“…Consultation of persons suspected of infection or infectious disease or those diagnosed with infection or infectious disease may be based on the results of tests available remotely [11] and can take place, particularly in large hospitals with a dispersed structure or between branches [61], especially in the initial phase, with the use of teleconferences or teleconsultations, supported by the hospital it system, securely transmitted between medical data units, as it is already practiced by multiple medical specialties [62][63][64] -which is conducive to the speed of response to the occurring circumstances and changes in the epidemiological situation [41].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies report effective use of applications in order to improve diagnostic and decision-making processes, for instance in the conditions of the operating theatre [ 8 ]. Cewe et al also showed that the necessary time to conduct a remote radiological consultation with the use of mobile devices compared to traditional description stations using the Picture Archiving and Communication System (PACS) is much shorter [ 9 ].…”
Section: Introductionmentioning
confidence: 99%